Demotivating Factors on English Speaking of English Program Students, Faculty of Education, Souphanouvong University - Souliya, Toulakone; Phanfongpet, Sipaseuth; Lamphaiphan, Ketsalinh; Sidavong, Khanthaly; Vatthanavong, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purpose of this study was to investigate the demotivating factors on English speaking of the students in English program Faculty of Education Souphanouvong University, the sample group of this study was 92 English program students which was selected by random. The research instrument was questionnaire designed by the researcher and compose of 5 factors as the characteristic and teaching style of the teacher, student factor, curriculum factor, social factor, classroom environment factor. The result exhibited that curriculum factor was the highest and the main demotivating factor caused English program students lost their motivation on English speaking in their classes while characteristic and teaching style of the teacher was the second range that was demotivating factor and followed by student factor, classroom environment was the last demotivating factor on English speaking of the students in English program faculty of Education Souphanouvong University.